Fetal Dysmorphology—Still an Essential Art. Analysis of the Limitations of Microarray in a Fetal Population and a Look Toward the Genome Sequencing Era. (July 2017) - Fletcher, E; Porteous, M; McKenzie, KJ; Maher, EJ; Evans, MJ
Cytogenomic microarray allows assessment of the genome at higher resolutions than traditional karyotyping. The objective of this study is to evaluate the utility of microarray in a routine fetal autopsy setting before the advent of routine fetal exome/genome sequencing and the issues these technologies may generate. A systematic review of fetal postmortems at 12–24 weeks gestation between January 2011 and December 2014 was undertaken. Cases where there was no consent for audit, research, or genetic testing were excluded as were cases referred to the Procurator Fiscal, stillbirths, and neonatal deaths. Copy number variations were detected in 16 cases. In addition, there was 1 case of uniparental disomy; not all of these were related to the phenotype. There were a number of cases with phenotypic abnormalities and normal array results. Five of these underwent directed mutation analysis—3 were positive. Genetic laboratory investigations such as microarray and Quantitative Fluorescent-Polymerase Chain Reaction may increase the diagnostic yield in the assessment of fetal dysmorphology. However, this study shows that genetic results not only require careful review given the potential uncertain significance but also require phenotypic assessment of the fetus by a competent fetal dysmorphologist to determine the likely causative effect of any detected anomaly. This best practice will also extend to next generation sequencing and interpretation of variants of unknown significance. Fetal medicine teams should ideally include specialists well versed in assessment of fetal anomaly to provide families with the best possible information about the cause of their pregnancy loss and their options for future pregnancies.